1990
DOI: 10.1021/ja00166a054
|View full text |Cite
|
Sign up to set email alerts
|

Interception of copper polysulfide clusters in the reaction of copper and sulfur in donor solvents: polysulfide complexes as the link between molecular and nonmolecular metal sulfides

Abstract: 253ChemInform Abstract If the reaction, which leads to CuS (covellite) at reflux temp., is carried out at 25 rc C a crystalline solid is obtained, which is identified as (IV) ( P21/n, Z=4). (IV) is an unusual example of a charge-neutral metal polysulfide complex shown to undergo ligand substitution reactions. For example, the pyridine ligand are exchanged with N-methylimidazole in Et2O reversibly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 0 publications
0
47
0
1
Order By: Relevance
“…[26] A recent report shows that the octasulfuido dianion is formed by the 2e ± reaction of S 8 in a donor solvent that contains sulfur. [18] Davis and Nakshbendi [26] reported that sulfur reacts with aliphatic primary and secondary amines to form colored solutions due to the stepwise nucleophilic attack of the S 8 rings by the amine, resulting in first the formation of N,N¢-polythiobisamines with in situ release of H 2 S, and then the progressive attack of the aliphatic amine by H 2 S to yield amine polysulfides. Similar to the case of liquid ammonia or n-butylamine, the sulfur-ethylenediamine solution here also contains various sulfur-amine species that would form sulfur-based radicals, which may play a role in the reaction with the elemental metals.…”
Section: Possible Reaction Mechanism Phase Formation and Transformamentioning
confidence: 99%
See 2 more Smart Citations
“…[26] A recent report shows that the octasulfuido dianion is formed by the 2e ± reaction of S 8 in a donor solvent that contains sulfur. [18] Davis and Nakshbendi [26] reported that sulfur reacts with aliphatic primary and secondary amines to form colored solutions due to the stepwise nucleophilic attack of the S 8 rings by the amine, resulting in first the formation of N,N¢-polythiobisamines with in situ release of H 2 S, and then the progressive attack of the aliphatic amine by H 2 S to yield amine polysulfides. Similar to the case of liquid ammonia or n-butylamine, the sulfur-ethylenediamine solution here also contains various sulfur-amine species that would form sulfur-based radicals, which may play a role in the reaction with the elemental metals.…”
Section: Possible Reaction Mechanism Phase Formation and Transformamentioning
confidence: 99%
“…We believe that the formation process of this molecular precursor is very similar to that of the reaction of metal with sulfur in donating solvents reported by Rauchfuss and co-workers. [18] Based on the results of TG-DTA, different phases of nickel sulfide nanoparticles can be obtained by controlling the thermal decomposition temperature and atmosphere. Figure 10 shows the XRD patterns of the Ni(en) x S y molecular precursor obtained at 160 C and the products obtained by vacuum thermal decomposition of it.…”
Section: An Alternative Route To Nickel Sulfide Nanoparticles By Decomentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Semiconductor transition-metal chalcogenides have been of much interest because of their excellent properties and potential applications. [10,11] Among these chalcogenides, copper sulfide is widely used as a thermoelectric cooling material, [12] optical filer, [13] optical recording material, [14] solar cell, [15] and superionic material. [16] Traditionally, copper sulfide was synthesized by a solid-state reaction of elements, [17] solid-state metathesis, [18] and self-propagating high-temperature synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Copper sulfide has attracted attention of many materials workers because of its unique properties and wide application in many fields, such as in thermoelectric cooling material, optical recording material, optical filter, solar cell, superionic materials, and the materials in chemical sensors [15][16][17][18][19][20]. Various kinds of structures of CuS have been synthesized recently.…”
Section: Introductionmentioning
confidence: 99%